Field-testing of the revised, draft South African Paediatric Food-Based Dietary Guidelines among Siswati-speaking mothers/caregivers of children aged 0–36 months in Kabokweni, Mpumalanga province, South Africa - I Möller; LM du Plessis; LC Daniels (The South African Journal of Clinical Nutrition, 2021)
Objectives: To determine the appropriateness and understanding of the revised, draft South African Paediatric Food-Based Dietary Guidelines (SA-PFBDG) among siSwati speaking mothers/caregivers of children aged 0–36 months. Previous exposure to guidelines with similar messages, barriers and enablers to following the guidelines were also assessed. Design: A descriptive, cross-sectional qualitative research approach was followed. Purposive and snowball sampling were used to recruit a total of 75 participants. Data were collected by means of focus-group discussions from 12 groups. Setting: Kabokweni, Mpumalanga, South Africa. Subjects: The study population included mothers/caregivers older than 18 years who provided informed consent. Results: The participants were generally aware of messages similar to those contained in the revised, draft SA-PFBDG. They reported exposure to these messages at clinics/hospitals, radio/television, and the Road-to-Health booklet. Participants showed good understanding of guidelines on breastfeeding, complementary feeding, inclusion of protein-rich and starchy foods as well as fruit and vegetables in the diets of young children as well as hygiene practices. The guidelines on avoiding tea, coffee and sugar drinks and high-sugar, high-fat salty snacks, being active and providing five small meals were less well understood. Enablers to following the guidelines were its perceived importance and positive impact on children's health. Barriers included misinterpretation of the guidelines and lack of money and resources. Conclusion: The revised, draft SA-PFBDGs are appropriate for the age group 0–36 months. A degree of rewording is suggested to aid understanding. The guidelines can be used as an educational tool to improve the nutritional status of children in South Africa.